2015
DOI: 10.1177/1947603515618483
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differential Genetic Response of Human Articular Cartilage to Impact Injury

Abstract: ObjectiveNormal physiological movement creates different weightbearing zones within a human knee: the medial condyle bearing the highest and the trochlea bearing the lowest weight. Adaptation to different physiological loading conditions results in different tissue and cellular properties within a knee. The objective of this study was to use microarray analysis to examine gene expression differences among three anatomical regions of human knee articular cartilage at baseline and following induction of an acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Several medical studies have reported increases in developmental control transcripts in response to stress such as injury of human knee articular cartilage [37], atherosclerotic-associated diseases [38], and lung cancer [39]. It is therefore, reasonable to suggest that increased abundance of developmental control and cancer-associated transcripts might reflect a universal response to stress that has not been previously recognized.…”
Section: Transcripts Of Developmental Control and Cancer-associated Imentioning
confidence: 98%
“…Several medical studies have reported increases in developmental control transcripts in response to stress such as injury of human knee articular cartilage [37], atherosclerotic-associated diseases [38], and lung cancer [39]. It is therefore, reasonable to suggest that increased abundance of developmental control and cancer-associated transcripts might reflect a universal response to stress that has not been previously recognized.…”
Section: Transcripts Of Developmental Control and Cancer-associated Imentioning
confidence: 98%
“…For example, molecular studies have been performed across a number of tissues to identify potential genetic signatures associated with musculoskeletal trauma. This includes investigation of a few select genes from meniscus tissue in both degenerative and acute traumatic injuries (77), different regions of articular cartilage following impact injury (78), and microarray analysis of ACL tissue at various postinjury time points (79). These approaches have been enhanced using high throughput RNA sequencing.…”
Section: Looking Ahead — Building On Existing Data By Alternative Stu...mentioning
confidence: 99%